'Deskless, commuteless, and theoretically omnipresent': work, global violence, and capitalist realism in Jennifer Egan's A Visit from the Goon Squad. Issue 9 (2nd September 2022) - White, Carl
ABSTRACT: This essay examines how, through narrating the white-collar workplace, Jennifer Egan's A Visit from the Goon Squad (2010) engages with structural concerns of contemporary capitalism, global violence, postcolonial oppression, and contemporary technologies as a text written in the wake of the 2007/8 financial crisis. Alongside these concerns and through reading two chapters of Egan's novel, 'Selling the General' and 'Pure Language', this article also examines how fictional representation more broadly operates as both an aesthetic mode and as an active component of a political-economic sensibility that is necessary to upholding the capitalist status quo in the contemporary moment: this is, as Mark Fisher describes, capitalist realism. By bringing these critical strands in dialogue with one another, not only does this enable a nuanced reading of how the novel understands and charts the relations between these structural concerns, but it also facilitates a furthering of capitalist realism as a critical framework.